Conservatism and innovation in the Hebrew language of the Hellenistic period: proceedings of a fourth International Symposium on the Hebrew of the Dead Sea Scrolls & Ben Sira - Joosten, Jan; Rey, Jean-Sébastien (Brill eBook titles 2008, 2008)
This volume contains 15 contributions addressing linguistic and philological issues. They seek to relate the Hebrew texts of the Hellenistic period to both earlier and later traditions. The papers deal with the Qumran scrolls, the Apocrypha and the Hebrew Bible